2020
DOI: 10.1097/sla.0000000000004077
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Positive Resection Margin in Laparoscopic and Open Liver Surgery for Colorectal Liver Metastases: A New Perspective in the Perioperative Assessment

Abstract: Objective: To assess the risk factors associated with R1 resection in patients undergoing OLS and LLS for CRLMs. Background: The clinical impact of R1 resection in liver surgery for CRLMs has been continuously appraised, but R1 risk factors have not been clearly defined yet. Methods: A cohort study of patients who underwent OLS and LLS for CRLMs in 9 European high-volume referral centers was performed. A mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
(127 reference statements)
2
16
1
1
Order By: Relevance
“…2,3 The cornerstone for a successful oncologic liver surgery relies on obtaining a R0 resection margin and preserving a proper healthy liver parenchyma to achieve better short-and long-term outcomes. 4,5 To achieve these goals, the application of intraoperative navigation tools has been required as a part of the progressive developments in liver surgery. In fact, the need of the real time visualization of precise liver anatomy, in particular during minimally invasive surgery (MIS), has encouraged the implementation of such instruments, potentially helpful for a proper and safe liver transection.…”
mentioning
confidence: 99%
“…2,3 The cornerstone for a successful oncologic liver surgery relies on obtaining a R0 resection margin and preserving a proper healthy liver parenchyma to achieve better short-and long-term outcomes. 4,5 To achieve these goals, the application of intraoperative navigation tools has been required as a part of the progressive developments in liver surgery. In fact, the need of the real time visualization of precise liver anatomy, in particular during minimally invasive surgery (MIS), has encouraged the implementation of such instruments, potentially helpful for a proper and safe liver transection.…”
mentioning
confidence: 99%
“…We showed that LLMS with ICG negative staining technique may ensure the complete curability of liver tumors, although some evidence showed positive resection margins (R1) in 6% of cases 23 . In contrast, Benedetti et al 24 reported that R1 resection was independent of the method of liver transection (open vs laparoscopy) as they showed R1 incidence of around 14% in both open resection and LLR. In our study, total R1 incidence of LLMS was 5.4%.…”
Section: Discussionmentioning
confidence: 78%
“…However, these studies mainly focused on minor liver resections without considering major hepatectomies 17 . Furthermore, Pringle's maneuver was used more and for longer time during mjLLR, which could be related to the necessity of avoiding oozing during LLR proceedings 23 . As previously reported, although Pringle's Maneuver tended to reduce blood loss, it is interesting that this aspect was more noticeable when performing mjLLR than mjOLR.…”
Section: Discussionmentioning
confidence: 98%
“…Based on the result of the survey, all procedures were performed with curative intent aiming for R0 resection, thus no debulking procedures were included. Surgical technique was comparable among all the participating centers and the laparoscopic approach for major liver resections has been previously described by many authors of our group 22,23 . Klatskin tumors and the need for vascular or biliary reconstruction were the main contraindications for LLR in cirrhotic patients.…”
Section: Methodsmentioning
confidence: 97%